Potential application of pig (Sus scrofa domestica) skin peptide-iron chelates in the treatment of iron deficiency anemia and regulation of intestinal flora metabolism - Huang, Shuteng; Deng, Hanxiu; Liang, Kexin; Zhao, Xue; Zhang, Jiayu (Frontiers in Nutrition, 2025)
Iron deficiency is an important public health concern worldwide. Intake of iron-fortified foods has been widely used to treat iron deficiency anemia (IDA). In this study, a novel food for iron supplementation was designed: pig (Sus scrofa domestica) skin peptide-iron (PSP-Fe) chelates. Structural characterization demonstrated that acidic amino acids (aspartic acid, glutamic acid) and aromatic amino acids (phenylalanine, tryptophan, and tyrosine) in PSP were involved in the chelation reaction, with the carboxyl group and amino group provided the major iron binding sites. In addition, iron significantly altered the microscopic morphology of PSP. IDA rats were established and different doses of iron supplements were gavaged for 21 days to evaluate the effectiveness of PSP in treating IDA. The medium dose of PSP-Fe restored hemoglobin (HGB), red blood cell (RBC), hematocrit (HCT), mean corpuscular hemoglobin concentration (MCHC), serum ferritin (SF), serum iron (SI), hepcidin, total iron binding capacity (TIBC) and transferrin saturation (TSAT) to normal levels. PSP-Fe also ameliorated the abnormal changes in heart coefficients, lungs coefficients, liver coefficients and spleen coefficients caused by IDA. PSP-Fe further restored iron storage in the liver and villous damage in the colon of rats compared to FeSO4. 16S rRNA results suggest that the 10 microbial markers in the Model group may impede iron absorption and HGB synthesis of host through biosynthesis of siderophore group nonribosomal peptides, vitamin B6 metabolism, lipoic acid metabolism, ascorbate metabolism and tryptophan metabolism. At the end, the safety of PSP-Fe was preliminarily affirmed by toxicity evaluation in vitro and in vivo. These findings suggest that PSP-Fe has potential as a novel functional food for treating IDA.